L’engagement et la responsabilité des interprètes en milieu social : les limitations de leur pouvoir - Kasperska, Iwona (Studia Romanica Posnaniensia, 2019)
This paper discusses the agency of community interpreters in a cross-cultural environment. Their empowerment is determined by several linguistic and extralinguistic factors, such as: mastering the language of communication by the speakers, social status of the languages used in multilingual countries, other parties’ behaviour, interlocutors’ different cultural backgrounds, interpreter’s loyalties (to the client and/or to the institution), and social norms of the speakers. This study deals with a number of communicative, social and pragmatic features, as well as it reveals the level of the interpreters’ power and responsibility for a successful outcome of communication. The main conclusion is that, even if traditionally they are depicted as a mere language conduits, neutral and invisible, the interpreters in social services turn out to be very visible actors. Their agency is flexible, e.i. it changes depending on the particular interaction, and their empowerment consists in making every communication as easy as possible for people deprived of such the agency.